Women in the classical world : image and text - Fantham, Elaine (Oxford University Press, 1994)
Information about women is scattered throughout the fragmented mosaic of ancient history. The vivid poetry of Sappho survived antiquity on remnants of damaged papyrus, riddled with gaps. The inscription on a beautiful fourth century B.C.E. grave praises the virtues of Mnesarete, an Athenian woman who died young, but we do not know if the grave's marble stele shows Mnesarete, or simply a ready-made design chosen by her family. We read that on one occasion in the fourth century a great number of Roman wives were given a collective public trial and found guilty of poisoning their husbands, but we can only guess whether these "poisonings" were invented, or were linked to a high occurrence of accidental food poisoning, or to something more sinister. Apart from the legends of Cleopatra, Dido, and Lucretia, and images of graceful maidens dancing on urns, the evidence about the lives of women of the classical world - visual, archaeological, and written - has remained little known and little understood. Now, the lavishly illustrated and meticulously researched Women in the Classical World lifts the curtain on the women of ancient Greece and Rome, from slaves and prostitutes, to Athenian housewives, to Rome's imperial family. The first book on classical women to give equal weight to written texts and artistic representations, it brings together a great wealth of materials - poetry, vase painting, legislation, medical treatises, architecture, religion and funerary art, women's ornaments, historical epics, political speeches, even ancient coins - to present women in the historical and cultural context of their time. Written by leading experts in the fields of ancient history and art history, women's studies, and Greek and Roman literature, the book's chronological arrangement allows the changing roles of women to unfold over a thousand year period, beginning in the eighth century B.C.E. The authors seek out and present ancient literature that preserves women's own voices. Both the art and the literature highlight women's creativity, sexuality and coming of age, marriage and child rearing, religious and public roles, and other themes. Fascinating chapters probe revealing aspects of the classical world: the ubiquitous reports of wild behavior on the part of Spartan and Etruscan women and the mythical Amazons; the changing views of the female body presented in male-authored gynecological treatises; the political and financial activities of women from all over Rome's empire; and the traces of upper and lower-class life in Pompeii, miraculously preserved by the eruption of Mount Vesuvius in 79 C.E. Provocative, surprising, filled with examples of the rich legacy of classical art, Women in the Classical World is a masterly foray into the past, and an important statement on the lives of women in ancient Greece and Rome